Perceived environmental barriers and facilitators of refugee children’s physical activity in/around refugee accommodation: a qualitative case study in Berlin - Chen, Siqi; Knöll, Martin (Archives of public health = Archives belges de santé publique, 2022)
Background Previous research have identified built environmental attributes associated with refugee children’s physical activity (PA); however, there is a lack of research focusing on refugee children’s environmental perceptions at the individual level. We examined the perceived environmental barriers and facilitators of refugee children’s PA. Methods Perceptions of PA environments by refugee children ( n = 15, 6 to 13 years old) and their parents ( n = 10) were captured by questionnaires and drawing workshops from one refugee accommodation in Berlin. Besides, photovoice was conducted with three children to obtain an in-depth understanding of their experiences of existing environments for PA. Research was applied between June and July 2019. All research material was transcribed and analysed using thematic analysis. Results Refugee children and their parents identified micro-environments as the centre of children’s daily PA, they usually played indoors but most parents perceived there was no spaces. In meso environments, children and parents thought there were insufficient spaces and were worried about neighbourhood safety. Furthermore, parents concerned more about ‘space accessibility’ for their children’s playing purposes instead of ‘space quality (e.g., equipment)’ . Children also indicated the importance of informal spaces for their PA. Conclusions Refugee children perceive a lack of space and safety when attempting to play in the existing micro and meso environments. Related practitioners should focus on providing more play spaces in micro environments and safe access to existing neighbourhood playfields. These efforts can augment much-needed research on strategies to better integrate refuge facilities to their urban context and essential in minimising current health and spatial inequality issues these vulnerable groups face across Germany and worldwide.